Remakes by B. Akunin - Skliarova, Tetiana; Skubachevska, Liubov (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The article considers the remake as a phenomenon of modern literature to reveal the work of B. Akunin. It is shown that the only text of Akunin, perceived by readers-researchers as a remake, is the play Seagull, which is a sequel to the Chekhov's work with the same name. Such perception was both a character of correlation with A. Chekhov's text (the last act of Chekhov's comedy is the first appearance of Akunin's play), and a provocative presentation (the play was released together with A. Chekhov's Seagull). The poetics of Seagull is noticeably oriented towards its perception as a sequel to Chekhov's text by the widest readership. However, in Akunin's practice, one can use works whose remake nature is far from being so obvious. First of all, we are talking about Decorator (a collection of Special Assignments), which can be read as a remake of Clean Monday by I. Bunin.As research shows, in The Decorator, the plot of Clean Monday is flattened and pointed. The motive of gaining the possession of beauty, which is one of the central ones in Bunin's story and determines the poetics of many levels of works, in Akunin's behavior performs an exclusively plot-forming function and determines the development of the detective line. The Bunin code also plays an important role in the first behavior of the Special Assignments collection - Spades Valet. As analysis shows, the poetics of the collection Special Assignments in an extremely simplified form mirrors the bipolar poetics of Bunin's artistic world.Likely an appeal to the Bunin code is demostrating the inferiority of a polar view of the world, from the one side, and a test of the possibilities of the poetics of the detective, on the other side.